L’etica e l’antropologia: Con particolare riferimento ai codici etici delle antropologie applicative - Colajanni, Antonino (Antropologia Pubblica, 2024)
The article provides a critical analysis of the complex relationship between ethics and anthropological research by focusing on the international literature and the ethical codes of the most important anthropological associations. Theoretical issues concerning ethics as a general problem of human conduct are often connected to those of anthropology' "responsibility" as a discipline applied in different contexts of violence, war, conflicts, interplaying with powers, institutions and the various "subjects" anthropologists study or work with. Through constant exchanges between the epistemological level of ethics and the comparison between different systems of social morality, anthropological associations produced specific ethical standards and codes by taking into account aspects such as privacy, consent to confidentiality, plagiarism and lack of transparency and the effects of the researcher or his/her scientific production on the broader society. Through a critical analysis of the main existing codes, the article will discuss the central points potentially conducive to an ethic code for the Italian Society of Applied Anthropology.